FORMULATION DEVELOPMENT OF COLON TARGETED MESALAMINE PELLETS: IN VITRO-IN VIVO RELEASE STUDY - BAHEKAR, JAGAN; WADHER, SHAILESH (International Journal of Applied Pharmaceutics, 2019)
Objective: This study was intended to investigate the potential of the colon specificity approach comprising of use of pH-sensitive and time-dependent polymers in combination for precise colonic release of Mesalamine or 5-Aminosalicylic acid (5-ASA). Methods: The extrusion and spheronization method, preferably employed in industry for allowing high dose capacity to formulate, was used to prepare drug pellets. The Wurster coating technique used for aqueous coatings of Eudragit NE 40D as an inner coat and Eudragit FS30D as outer coat. The changing pH media used for in vitro release study of optimization batches for both the coating levels. A scanning electron microscope (SEM) was used to evaluate coating thickness and surface morphology. Results: The pharmacokinetic parameters of formulation evaluated by in vivo study in rabbits revealed that the uncoated formulation released the drug too early in the gastrointestinal tract (GIT) with a mean Cmax of 1205.28±0.37 µg/ml at 2 h after administration, whereas desired lag time was achieved in case of coated pellets exhibiting mean Cmax 465.94±0.21 µg/ml and tmax of 8 h. Conclusion: The in vitro and in vivo release study divulge the reliability of approach involving the use of pH sensitivity and time dependency of polymer for drug release in a single formulation for the treatment of colonic diseases. Hence, the present study provides constructive results for colon targeting of 5-ASA pellets with industrially feasible processes.